Economic Study of 2-Stage Exchange in Patients With Knee or Hip Prosthetic Joint Infection Managed in a Referral Center in France: Time to Use Innovative(s) Intervention(s) at the Time of Reimplantation to Reduce the Risk of Superinfection - Serrier, Hassan; Julien, Christell; Batailler, Cécile; Mabrut, Eugénie; Brochier, Corinne; Thevenon, Sylvie; Maynard-Muet, Marianne; Henry, Agnes; Lustig, Sébastien; Huot, Laure; Ferry, Tristan; , The Lyon BJI Study group (Frontiers in Medicine, 2021)
Objective: Chronic prosthetic joint infections (PJI) are serious complications in arthroplasty leading to prosthesis exchange and potential significant costs for health systems, especially if a subsequent new infection occurs. This study assessed the cost of chronic PJI managed with 2-stage exchange at CRIOAc Lyon reference center, France. A threshold analysis was then undertaken to determine the reimbursement tariff of a hypothetical preventive device usable at the time of reimplantation, which possibly enables health insurances to save money according to the risk reduction of subsequent new infection. This analysis was also performed for a potential innovative device already available on the market, a dual antibiotic loaded bone cement used to fix cemented prosthesis that releases high concentrations of gentamicin and vancomycin locally (G+V cement). Method: Patients >18 years, admitted for a hip or knee chronic PJI managed with 2-stage exchange, between 2013 and 2015 were retrospectively identified. Following, resource consumption in relation to inpatient hospital stay, hospitalization at home, rehabilitation care, outpatient antibiotic treatments, imaging, biology acts, and consultations were identified and collected from patient records and taken into account in the evaluation. Costs were assessed from the French health insurance perspective over the 2-years following prosthesis reimplantation. Results: The study included 116 patients. Mean cost of PJI was estimated over the 2-years following prosthesis reimplantation at €21,324 for all patients, and at €51,697 and €15,745 for patients with (n=18) and without (n=98) a subsequent new infection after reimplantation, respectively. According to the threshold analysis the reimbursement tariff: (i) should not exceed €2,820 for a device which can reduce the risk of a new infection by 50% and; (ii) was between €2,988 and €3,984 for the G+V cement (estimated risk reduction by 80%). Conclusion: Chronic PJI requiring a 2-stage revision is costly, with significant costs in relation to the reimplantation procedure (about 15 k€). However, following reimplantation the rate of subsequent new infection remained high, and the cost of reimplantation following a new infection is considerable, reaching 50k€ per patient. These first cost estimates of managing chronic PJI with 2-stage exchange in France underline the economic interest of preventing new infections.